Komunikasi Interpersonal dalam Keharmonisan Hubungan Pernikahan Pada Individu Dewasa Muda di Kelurahan Pulogebang - Yulianta, Nana; Wulandari , Yulianti Fajar; Himawan , Sultan (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This study investigates the role of interpersonal communication that influences marital relationship harmony among young adults in Pulogebang Subdistrict. The primary objective of this research is to understand how effective interpersonal communication contributes to the formation and maintenance of harmonious marital relationships amidst the complexities of urban life. The findings indicate that effective interpersonal communication involves active listening, mutual respect, and honest, open communication. These factors play a crucial role in enhancing the quality of marital relationships, strengthening emotional bonds between partners, and reducing potential harmful conflicts. This research aims to provide both theoretical and practical contributions by expanding our understanding of the importance of interpersonal communication in supporting marital relationship sustainability. It is hoped that this study will serve as a reference for public policy and further research development in the fields of interpersonal communication and marital life.